PENGGUNAAN PESTISIDA DAN IMPLIKASINYA BAGI KESEHATAN PETANI DI KABUPATEN TIMOR TENGAH SELATAN, NUSA TENGGARA TIMUR - Rully Adi Nugroho (Scripta Biologica, 2018)
Pesticides pose a risk to public health and environmental in agricultural areas. This study described pesticide use among farmers in Oebobo, Batnun, Tupan and Pollo villages, South Central Timor, Indonesia. Some 400 farmers were interviewed about pesticide use, knowledge and attitude, symptoms of intoxication, personal protective equipment and hygiene. The farmers had adequate knowledge about pesticide toxicity, but farmer’s awareness did not necessarily translate into action. Majority did not use appropiate personal protective equipment nor good hygiene when handling pesticides. Farmers in South Central Timor did not use the most hazardous pesticides (class Ia and Ib). However, use of class II pesticides and those of lower toxicity in combination with inadequate practice among farmers was found in the study areas. Expensive protective equipment and behavioral patterns, such as spraying without protective clothing and mixing pesticides with bare hands combine to produce several well-documented health problems. Therefore, alternative crop management systems which could help preventing the negative effects of pesticides on farmer health and the environment are needed. Training farmers in integrated pest management methods, use of proper hygiene and personal protective equipment when handling pesticides should be promoted.